Impact of complete vaccination againts COVID-19 on lethality and deaths per million habitants in Europe 06/05/2022 - Mora-Alvarado, Darner A. (2023)
The present study addresses the impact of complete vaccination-with two doses-against COVID-19 in 47 European nations, on lethality and mortality/million inhabitants up to 06/05/2022, by applying the linear correlation coefficient of Pearson at 95% confidence between the percentages of the population with general lethality or deaths/confirmed cases x 100 and deaths/million inhabitants. The results indicate that: the “r” value of association or linear correlation between vaccination with case fatality rates and deaths/million population was -0.63 and -0.26, which is a strong inverse association. with lethality and a moderate inverse correlation with deaths/million in the European countries studied. The comparison of the “r” values of linear correlation with the other continents, show that the lower inequality in Europe in complete vaccination against COVID-19, is reflected with greater inverse strength between the association of vaccination variables with fatalities. and deaths/million inhabitants.